A glitch in the matrix: Age‐dependent changes in the extracellular matrix facilitate common sites of metastasis. Issue 1 (7th October 2020) - Marino, Gloria E.; Weeraratna, Ashani T.
Abstract: People over 55 years old represent the majority of cancer patients and suffer from increased metastatic burden compared to the younger patient population. As the aging population increases globally, it is prudent to understand how the intrinsic aging process contributes to cancer progression. As we age, we incur aberrant changes in the extracellular matrix (ECM) of our organs, which contribute to numerous pathologies, including cancer. Notably, the lung, liver, and bone represent the most common sites of distal metastasis for all cancer types. In this review, we describe how age‐dependent changes in the ECM of these organs influence cancer progression. Further, we outline how these alterations prime the premetastatic niche and why these may help explain the disparity in outcome for older cancer patients. Abstract : Patients over 55 years old constitute the majority of the cancer patient population and suffer from increased metastatic burden compared to younger patients. However, it is largely unclear what role aging may play in this disparity. The natural aging process imparts detrimental changes in the extracellular matrices of all organs. These changes promote organ dysfunction, age‐related pathologies, and cancer progression. We proffer that the aging process both helps form the premetastatic niche at common organ sites and facilitates metastatic outgrowth at these sites.